Real Time Face Recognition Attendance System Using Python and OpenCV - Yap, Jin Wei; Jawad, Mohammed Saeed (Applied Information Technology And Computer Science, 2024)
The Real Time Face Recognition Attendance System using Python and OpenCV is a desktop application that utilizes facial recognition technology to track and manage attendance. The system was developed to improve on the weaknesses of existing attendance management methods which use manual and paper as the medium for attendance management. A prototype model was used to develop this project. Meanwhile, system development is achieved by using VS Code software and a MySQL database. The programming language used is Python and the face recognition algorithm uses the Local Binary Pattern Histogram (LBPH). The face detection is implemented by using the Haar Cascades classifier for object detection. In general, this system can help improve the effectiveness and efficiency of data management in educational institutions and keep it under control in an organized manner.